Electron transport through NiSi2–Si contacts and their role in reconfigurable field-effect transistors. (17th June 2019) - Fuchs, Florian; Gemming, Sibylle; Schuster, Jörg
Abstract: A model is presented which describes reconfigurable field-effect transistors (RFETs) with metal contacts, whose switching is controlled by manipulating the Schottky barriers at the contacts. The proposed modeling approach is able to bridge the gap between quantum effects on the atomic scale and the transistor switching. We apply the model to transistors with a silicon channel and NiSi2 contacts. All relevant crystal orientations are compared, focusing on the differences between electron and hole current, which can be as large as four orders of magnitude. Best symmetry is found for the orientation, which makes this orientation most advantageous for RFETs. The observed differences are analyzed in terms of the Schottky barrier height at the interface. Our study indicates that the precise orientation of the interface relative to a given transport direction, perpendicular or tilted, is an important technology parameter, which has been underestimated during the previous development of RFETs. Most of the conclusions regarding the studied metal-semiconductor interface are also valid for other device architectures.